Implementation of The Maluku Innovation and Creativity Program (Kreasiku) In Maluku Province - Labetubun, Feronika; Madubun, Jusuf; Latuconsina, Nurainy (Journal of Government Science Studies, 2025)
This research is a descriptive qualitative study aimed at examining the implementation process of the Maluku Innovation Creativity Program (Kreasiku). The program is designed to facilitate innovation development clinics for Regional Apparatus (PD), both at the provincial district and city levels, as well as as a reference for annual innovation. At the provincial level, the program focuses on developing policies that can be implemented more widely, while at the district and city levels. The results indicate that the program has received support from the Maluku Provincial Government in response to regulations concerning local government and innovation. However, the implementation of the program has faced several challenges, such as a lack of resources and resistance to change. Nonetheless, the program has produced several innovations that have positively impacted the quality of public services and the image of Maluku Province as an innovative region. Therefore, this study concludes that the (Kreasiku) has the potential to support the acceleration of bureaucratic reform and the enhancement of public service quality in Maluku Province.